The Attitude of Portuguese Physical Education Teachers toward Physical Fitness - Adilson Marques; Diogo Balsa; Marta Domingos; Rafael Cavalheiro; Tiago Carreira; Tiago Moreira; Tiago Ribeiro; Élvio R. Gouveia (MDPI AG, 2022)
In this study, we aimed to examine how Portuguese physical education teachers perceive the development of physical fitness through fitness tests in schools. The participants were 764 Portuguese teachers teaching at middle-school and high-school levels. The Physical Education Teacher Attitudes Toward Fitness Tests Scale (PETAFTS) was used to collect the data. The means and confidence intervals for each attitude subdomain and the overall attitude were computed. A one-way ANOVA was used to examine the group differences in three subdomains of the attitudes of teachers by different variables. The overall attitude of teachers toward fitness tests was slightly positive according to a 7-point Likert scale (5.52, 95% CI: 5.47, 5.58). The results suggested that female teachers found fitness tests more useful, but male teachers significantly enjoyed implementing them. The data collected also showed that younger teachers found the implementation of fitness tests significantly more enjoyable than older teachers. In conclusion, future research should prioritise specific intervention content considering gender and the age of teachers to reinforce the development of physical fitness through fitness tests in schools.